Estimation of Genetic Parameters for Selected Quantitative Traits in Introduced African Yam Bean (Sphenosylis stenocarpa Hochst. ex. A. Rich Harms) Genotypes - Emmanuel Norman, Prince; Yannah Karim, Kumba; Sylvia Gloria Ethel Norman, Yvonne; Lonaah Vamboi, William (Journal of Tropical Crop Science, 2023)
A solid understanding of the genetic control of traits within breeding populations is essential for selecting superior genotypes and parent plants for African yam bean (AYB) cultivation. In this study, we explored the phenotypic breeding values and genetic parameter estimates for various traits in 10 introduced AYB varieties. These traits included seed emergence speed (SES), seedling vigor index (SVI), final germination percentage (FGP), seed yield, days to first flower bud initiation (DAYSFBI), days to first flowering (DAYSF), and days to first pod initiation (DAYSPI). We conducted the trial using a randomized complete block (RCB) design with the following varieties: TSs2, TSs60, TSs11, TSs33, TSs282, TSs450, TSs10, TSs432, TSs424, and TSs151B. Traits showing high and medium genotypic coefficient of variation (GCV) were seed yield (20.7), SVI (12.1), and seed emergence speed (10.8), respectively. Traits with high phenotypic coefficient of variation (PCV) included seed yield (36.8), SVI (22.8), and SES (37.5). The presence of variability in all studied traits was evident from both GCV and PCV values. However, PCV values were slightly higher than GCV, suggesting the influence of environmental factors on these traits. Seed yield exhibited high genetic advance (23.9) and intermediate heritability (31.5%), while SES showed low heritability (8.4%) and low genetic advance (6.5), and FGP displayed low heritability (8.3%) and low genetic advance (2.1). High heritability and genetic advance in certain traits indicate the presence of additive gene action, suggesting that these traits can be improved through direct selection. These findings suggest the presence of valuable variations that can be harnessed for AYB genetic enhancement and selection purposes. Our study results offer valuable insights for the genetic improvement, conservation, management, multi-location evaluations, short-term recommendations, and potential release of new AYB genotypes.